CRYOBALLOON ABLATION IN RUSSIAN SITES OF INTERVENTIONAL ATRIAL FIBRILLATION MANAGEMENT TREATMENT: RESULTS OF THE FIRST NATIONWIDE SURVEY - E. N. Mikhailov; D. S. Lebedev; E. A. Pokushalov; K. V. Davtyan; E. A. Ivanitsky; A. A. Nechepurenko; A. Ya. Kosonogov; G. V. Kolunin; I. A. Morozov; S. A. Termosesov; E. B. Maykov; D. N. Khomutinin; et al. (Российский кардиологический журнал, 2015)
Aim. The results of cryoballoon ablation (CBA) are known from the studies performed in the experienced centers of catheter treatment of atrial fibrillation (AF). The current study presents the results of CBA in real practice in centers with various experienceMaterial and methods. Among 62 Russian sites performing catheter treatment of AF, in 15 the CBA methods were in use to isolate pulmonary veins, in the years 2012-2014. Centers staff were surveyed for the detailed description of all performed CBA till 10.2014. The questionnaire included 74 lines about the centers experience, patients properties and ablation procedures, management of patients and complications. At the second step the questionnaire was used about complications.Results. Thirteen centers provided full data on all patients with CBA (457 procedures; 94% for paroxysmal AF; >95% CBAs in Russia). Six centers were marked as highly experienced for CBA for AF (mean 414,2±339,4 ablations for AF per year), and 7 — with lesser experience (33,2±34,3 ablations for AF per year). Ten centers provided the results of 6/12 month observation, and 11 centers — detalization of the complications data. there were no statistically significant differences in arrhythmia absence in patients from both types of centers (61,9±10,0 versus 61,3±30,4%). Serious complications developed in 1,5% of patients (4 tamponades, 2 strokes and 1 diaphragmal nerve palsy) and were similarly spread among more and less experienced centers (1,4% vs. 2%, p>0,05). Minor adverse events (vascular, transient diaphragm nerve palsy, transient hemoptysis) were found in 37 (8%) patients and were more common in more experienced (teaching) centers. Overall frequency of adverse events and of vascular events was higher in females than males (12% and 4,9% vs. 6% and 0%, resp.; p<0,05).Conclusion. In the real clinical practice CBA is performed with acceptable efficacy and moderate frequency of adverse events development. In less experienced centers of catheter treatment of AF the prevalence of serious adverse events does not differ from less experienced. Women develop vascular complications more often.